Beyond Journalism, Beyond Naturalism: Sarah Kane’s Attempts on Truth - Carrasco Coquillat, David (Journal of Artistic Creation and Literary Research, 2025)
The British playwright Sarah Kane (1971–1999) became one of the most celebrated and derided authors in the 1990s theatrical scene in Great Britain, to a large extent due to the vitriolic response offered by many tabloid journalists and theater critics to her first play, Blasted (1995). This paper explores the reaction by the British press to her plays, at the same time that it studies the portrayal of mass media in Sarah Kane’s oeuvre by examining how Kane criticized the distorting effects of the media on the depiction of truth, offering a theatrical approach based on honesty and violence as an alternative to the affect-stripping tactics of journalism. Sarah Kane’s works are analyzed in the context of the rejection of naturalism that is present in all her plays, a naturalism which is seen as a byproduct of the mimetic depiction of reality championed by journalism. Truth is seen by Sarah Kane’s characters, including Hippolytus in Phaedra’s Love (1996), as a radical ideal worth pursuing despite the devastating effects it has on its advocates, who, most noticeably in her latest plays, Crave (1998) and 4.48 Psychosis (2000), are destroyed in the process of trying to reach honesty and communicate an inner feeling about themselves. The choice of a surreal and minimalistic approach both in the language used by the characters and the staging of the plays is seen as a response to a culture saturated by mediated content, in which the failure of words to convey sense adds to the inadequacy of mimetic representations to express affection.